MIDDLE MIOCENE TO HOLOCENE GEOLOGICAL HISTORY AND POTENTIAL OF BABAKAN JAWA AREAS, MAJALENGKA DISTRICT OF WEST JAVA-INDONESIA - Ambari, Wardahrose Dhifa; Sunardi, Edy; Ilmi, Nisa Nurul (Universitas Padjadjaran, 2026)
Geological mapping activities were conducted in the Sidamukti, Babakan Jawa, Cibodas areas and surroundings, Majalengka District, West Java Province. The main objective of this research is to determine the geomorphological characteristics, lithology, geological structures, and geological potential in the research area. The methods used include field observations, laboratory analysis, interpretation of topographic maps and satellite imagery, as well as structural analysis using stereonet. The research results show that the geomorphology of the study area was formed by the interaction of endogenic forces (tectonic and volcanic) and exogenic forces (weathering and erosion), resulting in five main geomorphological units. The stratigraphy of the area consists of five rock units composed of claystone units from the Middle Miocene to Holocene alluvial deposits. The developed geological structures indicate the influence of extensional stress with a strike-slip component that forms normal faults and reverse faults trending northwest–southeast. The geological potential of the area includes resources such as andesite stone, sand, and gravel, as well as the geotourism potential of Taman Gunung Batu Karang. On the other hand, steep hilly areas with weathered lithology show vulnerability to mass movements, making them landslide-prone areas. The results of this mapping are expected to serve as a basis for sustainable natural resource management and geological disaster mitigation.